Faktor yang Mempengaruhi Tingkat Kecurangan Karyawan PT. BUM Pabrik Perikanan Samudera Kendari - Oktaviana, Rieski Dwi (CV. Kurnia Grup, 2023)
The purpose of this study is to provide empirical evidence of the influence of employee attitudes toward fraud on PT. BUM Kendari ocean fisheries, provide empirical evidence of the effect of pressure on the employee to fraud PT. BUM Kendari ocean fisheries, provide empirical evidence influence employees the opportunity to fraud at PT. BUM Kendari ocean fisheries, provide empirical evidence of the influence of employee capability to fraud at PT. BUM Kendari ocean fisheries, provide empirical evidence influence attitudes, the pressure occasion, and employee capability simultaneously to fraud on PT. BUM Kendari ocean fisheries. The population in this study were employees of PT. BUM Kendari ocean fisheries as many as 42 employees. The sampling technique using census method. Census method is sampling technique when all members of the population used as a sample. The analysis tool used is the Multiple Linear Regression Analysis. The results showed that There is a significant influence on the attitude (Rationalization) against fraud with a significance value of 0.045. There is a significant influence of pressure against fraud with a significance value of 0.008. There is a significant influence of opportunities against fraud with a significance value of 0.027. There is a significant influence on the capability of the fraud with a significance value of 0.002. There is a significant influence on the attitude (Rationalization), Pressure, opportunity and capability against fraud with a significance value of 0.009.